Gut microbiota and protein-to-protein ratios in NAFLD: insights from Mendelian randomization and murine studies - Lei, Langhuan; Shi, Wei; Yang, Xing; Lin, Jiali; Liang, Qiuyu; Huang, Xiaozhi; Pan, Liuxian; Li, Wei (Frontiers in Nutrition, 2025)
BackgroundGut microbiota and protein metabolism play critical roles in non-alcoholic fatty liver disease (NAFLD) progression, but their causal relationships remain unclear. This study integrates Mendelian randomization (MR) analysis and experimental validation to identify microbial and molecular contributors to NAFLD and explore potential therapeutic targets.MethodsTwo-sample MR analysis was performed to assess the causal effects of gut microbiota and protein-to-protein ratios on NAFLD using inverse variance-weighted, maximum likelihood, MR-Egger, weighted median, weighted mode, and Wald ratio methods. Sensitivity analyses were conducted to ensure result robustness. Mediation analysis was applied to examine whether protein-to-protein ratios mediate the link between gut microbiota and NAFLD.ResultsMR analysis identified 19 gut microbial taxa and 148 protein-to-protein ratios significantly associated with NAFLD. Additionally, 49 significant mediation relationships were identified, where seven gut microbial taxa influenced NAFLD via 45 protein-to-protein ratios. MR analysis identified 38 proteins significantly associated with NAFLD, derived from 192 unique proteins involved in 148 NAFLD-related protein-to-protein ratios. Experimental validation confirmed the protective role of Lactobacillus salivarius, which alleviated hepatic lipid accumulation, improved glucose-lipid metabolism, and reduced inflammatory cytokine expression. Among the identified targets, the hepatic mRNA expression levels of ANGPT1, SKAP2, SPARC, and STAMBP were significantly upregulated in NAFLD tissues and were markedly reduced following Lactobacillus salivarius supplementation.ConclusionThis study establishes a causal link between gut microbiota, protein metabolism, and NAFLD, identifying microbial and molecular targets for intervention. The findings support microbiota-based therapies and protein biomarkers for NAFLD management, warranting further clinical validation.